Diversification of activity in the context of companies life cycle - Ilona Kutut; Romualdas Ginevičius; Vladislavas Kutut (Business: Theory and Practice, 2008)
Many small businesses grow by taking opportunities to diversify, although there are risks because of limited resources on all fronts. Businesses should weigh up the risks and costs of opting for growth carefully against the benefits. Diversification can take several forms, including new, related products or services to existing customers, new markets for existing products, new products for new markets. But the aim of every company is to decide when and how to diversify. Analysis of literature helps us to understand that finding best moment for diversification is related to the product or companies life cycle. Business diversification is one of the companies growth strategies and correlates with corporate life-cycle theory. Corporate life-cycle theory is an extension of the product life-cycle concept developed in marketing. But there exist at least two problems in employing the concept. Firstly, there is no consensus on the definition of life-cycle model. And secondly, there is no consensus on the methodologies of identifying each life-cycle stage. Author is trying to find such methodology and adapt it to Lithuanian economic situation.